Clinical and mycological characteristics of keratitis caused by Colletotrichum gloeosporioides: A case report and review of literature - Alireza Izadi; Mohammad Soleimani; Roshanak Daie Ghazvini; Seyed Jamal Hashemi; Mohssen Gramishoar; Kazem Ahmadikia; Mehdi Aminizadeh; Mohammad Ghahri; Zohre Abedinifar; Aleksandra Barac; Sadegh Khodavaisy (Journal of Infection in Developing Countries)
Introduction: Colletotrichum species are well-known plant pathogens, which have been increasingly reported as the cause of keratitis or subcutaneous lesions in humans. In this study we reported a rare case of fungal keratitis from Iran and reviewed the literature.